The Effect of Reproductive Health Education on the Knowledge Level of Adolescent Pre-Marriage Sex in Riau Province, Indonesia - Putri Ramadanti Setiawati; Tyas Aisyah Putri; Khoiriyah Isni (Universitas Ahmad Dahlan, 2023)
Background: Adolescence is a stage of growth and development in humans that occurs after childhood and before adulthood. Adolescent will experience emotional changes and want to know new things that tend to be at risk of falling into promiscuity that leads to pre-marital sexual behavior. Lack of knowledge of adolescents about reproductive health is one of the contributing factors. Therefore, it is necessary to conduct research on the effect of reproductive health education on the level of knowledge on preventing adolescent premarital sex in students of Junior High School Dwipa Abadi Kateman. Methods: This research method uses a one group pretest-posttest design. Respondents used were students in grades 7, 8, 9 Junior High School Dwipa Abadi Kateman as many as 50 students. The intervention provided was in the form of health education in one meeting for 1 hour. The Wilcoxon Sign Rank Test was performed to analyze the data. Results: Before being given the reproductive health education intervention, 31 people (62%) had high knowledge and after being given the reproductive health education intervention there were 44 people (88%) had high knowledge. From the results of the Wilcoxon Sign Rank test, a p-value of <0.001 was obtained, indicating that there was a difference in knowledge before and after the intervention. Conclusion: There was an increase in adolescent knowledge about health after being given education regarding the importance of maintaining reproductive health in adolescents at SMP Dwipa Abadi Kateman.